(untitled) (Research, Society and Development, 2021)
Objectives: To draw attention to the importance of following up children with congenital syphilis and to present an unusual case of bone changes that persisted up to 7 years of life. Methods: Observational, descriptive and retrospective study using medical records review of three patients with congenital syphilis and literature search, using the Uptodate, PubMed, Medline, Lilacs, Scielo databases covering the period from 2015 to 2021. Results: We describe 3 sisters. with congenital syphilis that were diagnosed and treated at birth and the first-born, rescued at age 7, complained of severe pain when moving her lower limbs since age 5 years. At birth he had VDRL 1:4; non-reactive VDRL parent (NR); mother with VDRL 1:16 and inadequately treated during pregnancy. The first-born had metaphyseal alterations and VDRL in negative CSF, being treated with crystalline penicillin for 10 days, however, she did not comply with outpatient follow-up. During this hospitalization, the physical examination showed no alterations, VDRL NR and long bones radiography with lytic image in the left and right legs suggestive of syphilis. Hospitalization was indicated and treatment with crystalline penicillin 50,000 IU/kg/dose was performed, 6/6 hours for 10 days. At 8 years and 4 months, he no longer had bone changes or pain symptoms when walking. In the second pregnancy she had adequate treatment and in the third pregnancy the father was not treated and the mother received only one dose of medication. The two conceptuses contracted congenital syphilis with bone changes at birth which, in the follow-up at 24 months and 6 months of life, respectively, were no longer detected. Conclusions: The follow-up of children with congenital syphilis should be carried out until all clinical, laboratory and radiological alterations disappear. This case series highlights the importance of diagnosing and treating pregnant women and their sexual partner(s) to eliminate mother-to-child transmission as well as the diagnosis at birth of cases of congenital syphilis and adequate treatment and follow-up.